Improved Disease-free Survival After Prehabilitation for Colorectal Cancer Surgery. Issue 3 (September 2019) - Trépanier, Maude; Minnella, Enrico M.; Paradis, Tiffany; Awasthi, Rashami; Kaneva, Pepa; Schwartzman, Kevin; Carli, Franco; Fried, Gerald M.; Feldman, Liane S.; Lee, Lawrence
Abstract : Objective: The objective of this study was to investigate the effect of prehabilitation on survival after colorectal cancer surgery. Summary of Background Data: Preoperative multimodal exercise and nutritional programs (prehabilitation) improve functional capacity and recovery following colorectal surgery. Exercise may also affect cancer outcomes by mediating the systemic inflammatory response. The effect of prehabilitation on cancer outcomes is unknown. Methods: Pooled data from 3 prehabilitation trials (2 randomized controlled trials, 1 cohort) in patients undergoing elective, biopsy-proven, primary non-metastatic colorectal cancer surgery from 2009 to 2014 within an enhanced recovery program were analyzed. Patients were grouped into +prehab or–prehab. The primary outcomes were 5-year disease-free (DFS) and overall survival (OS). DFS and OS were analyzed using Kaplan-Meier curves and multiple Cox regression. Results: A total of 202 patients were included (+prehab 104, –prehab 98). Median prehabilitation duration was 29 days (interquartile range 20–40). Patient and tumor characteristics were well-balanced (33% stage III). Postoperative complications and time to adjuvant chemotherapy were similar. Mean duration of follow-up was 60.3 months (standard deviation 26.2). DFS was similar for the combined group of stage I–III patients ( P = 0.244). For stage III patients, prehabilitation was associated with improved DFS (73.4% vs 50.9%, P = 0.044). There were no differences in OS ( P = 0.226). Prehabilitation independently predicted improved DFS (hazard ratio 0.45; 95% confidence interval, 0.21–0.93), adjusting for stage and other confounders. Prehabilitation did not independently predict OS. Conclusion: In this report, prehabilitation is associated with improved 5-year DFS in stage III colorectal cancer. This finding should be confirmed in future trials. Abstract : Supplemental Digital Content is available in the text